The Improvement and Internationalization of China’s Biosafety Diversity Legal System from the Perspective of the "Belt and Road Initiative" - Lu, Xianghe (International Journal of Social Sciences and Public Administration, 2024)
The protection of biosafety diversity is of great importance on a global scale, and plays a key role in maintaining ecological balance and promoting sustainable development. The "Belt and Road Initiative" has brought new opportunities and challenges to the protection of biosafety diversity, and the legal system of biosafety diversity in China should be adjusted and improved accordingly. Reviewing the development process and current situation of China’s biosafety diversity legal system, it can be concluded that there are problems and deficiencies in the current legal system, such as the imperfect legal system, insufficient law enforcement, and insufficient international cooperation, and measures should be taken to strengthen the construction of the legal system, increase law enforcement, and strengthen international cooperation. At the same time, we should also pay attention to the path of internationalization of China’s biological safety diversity legal system, including active participation in international negotiations and cooperation, strengthening international exchanges and cooperation, and promoting the improvement of the international legal system.